A synchronic lexical study of the Ede language continuum of West Africa: The effects of different similarity judgment criteria - Kluge, Angela (Afrikanistik online, 2008)
In the context of a synchronic lexical study of the Ede varieties of West Africa, this paper investigates whether the use of different criteria sets to judge the similarity of lexical features in different language varieties yields matching conclusions regarding the relative relationships and clustering of the investigated varieties and thus compatible recommendations for further sociolinguistic research. Word lists elicited in 28 Ede varieties were analyzed with the inspection method. To explore the effects of different similarity judgment criteria, two different similarity judgment criteria sets were applied to the elicited data to identify similar lexical items. The quantification of these similarity decisions lead to the computation of two similarity matrices which were subsequently analyzed by means of correlation analysis and multidimensional scaling. The analysis findings suggest compatible conclusions regarding the relative relationships and clustering of the investigated Ede varieties. However, the matching clustering results do not necessarily lead to the same recommendations for more in-depth sociolinguistic research, when interpreted in terms of an absolute lexical similarity threshold. The indicated ambiguities suggest the usefulness of focusing on the relative, rather than absolute in establishing recommendations for further sociolinguistic research.
Keywords: Ede; Nigeria; Yoruba